3D segmented model of head for modelling electrical activity of brain - Egill A. Friðgeirsson; Paolo Gargiulo; Ceon Ramon; Jens Haueisen (PAGEPress Publications, 2012)
Computer simulation and modelling of the human body and its behaviour are very useful tools in situations where it is either too risky to perform an invasive procedure or too costly for in vivo experiments or simply impossible for ethical reasons. In this paper we describe a method to model the electrical behaviour of human brain from segmented MR images. The aim of the work is to use these models to predict the electrical activity of human brain under normal and pathological conditions. The image processing software package MIMICS is used for 3D volume segmentation of MR images. These models have detailed 3D representation of major tissue surfaces within the head, with over 12 different tissues segmented. In addition, computational tools in Matlab were developed for calculating normal vectors on the brain surface and for associating this information to the equivalent electrical dipole sources as an input into the model.